ANALISIS KELAYAKAN FINANSIAL USAHA TERNAK AYAM RAS PETELUR UNGGAS KENYUM DI KAMPUNG MUARA PRAFI DISTRIK MASNI KABUPATEN MANOKWARI - Esti Pratiwi; Ishak Suwardi; Diana N. Irbayanti (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2020)
Manokwari is one of the producers of chicken eggs in West Papua province. The need for nutritious food is especially foods that contain protein today. This makes the need for chicken eggs to increase with the growth of the people of Manokwari. It is necessary to increase the population of laying chickens to meet the needs in Manokwari especially in Masni district. The addition of the population can be either DOC or Layer, so it is necessary to analyze financial feasibility to determine if the population increase is feasible from financial aspects. This research was conducted on poultry hatchling in the village of Kenyum Fowl in the Kampung Muara Masni District which assumed a bias for the addition of livestock as many as 1,220 laying chickens. This research was conducted on the efforts of poultry chicken laying in Kenyum for 2 weeks, starting from 23 December 2019 until 5 January 2020. The method used is a quantitative method with a case study approach. The subject in this study is the business owner of Poultry Egg laying chicken Kenyum. The sampling method performed is intentionally (purposive). The data collected in this study is primary data and secondary data. The results of this study stated that the business of Kenyum poultry in katakana deserves to be carried out from the financial aspect, both in DOC and layer additions. This is because assessments made using investment criteria show good results or qualify for eligibility. The value of Payback Period (PP) or the rate of return for 3 years 8 months for addition in the form of layers and 2 years 8 months for the addition of layers, and both are not more than the age of business is 5 years. The value of Net Present Value (NPV) produced in the business of poultry chicken egg laying Kenyum at a deposit interest rate of 5.5% is 331,899,382 for additions in the form of DOC and 2,259,789,228 for the addition of layers. The IRR (Internal Rate of Return) value for the addition of DOC is 22.54% and 89.37% for adding layers. As well as the Profitabillity Index (PI) value of 1.84 and 6.710.